The Use of Lafaz Amar on Ijtihad Madhhab towards the Effect of the Salat Law (Study of Ushul Fiqh) - Munawir Sajali (Britain International for Academic Research (BIAR) Publisher, 2021)
Lafaz amar is a study of ushul fiqh that has been explained by the scholars in their books, and lafaz amar also has various forms and types in the Qur’an and hadith, so that it will have different understandings among scholars when understanding these words of amar, however After conducting the research, based on the description and analysis carried out as explained regarding the use of lafaz amar in the Imam Madhhab's ijtihad and its effect on prayer, several conclusions can be drawn as follows: prayer there are 5 forms of lafaz amar used, namely the form of fi'il amar mufrad, fi'il amar jama, 'fi'il mudhari with lam amar, using fi'il madhi and using the word عَلَى. Whereas users of lafaz amar in the 4 books of the 4 Madhhab s of fiqh scholars, from this research there are also 5 forms of lafaz amar in general, but each Madhhab has differences in the form of lafaz amar which is used as arguments, such as the hanafi Madhhab in his book Hâsyiah Ibn 'Âbidîn has 4 forms of amar lafaz, namely fi'il amar mufrad, fi'il amar jama', lafaz amar fi'il madhi with lafaz كُتِبَ, أُمِرْتُ and lafaz amar using lafaz عَلَيْكُمْ, so on the Madhhab Mal Fiiki in his book Al-Kâfî Fî Fiqh Ahli Al-MadînahAl-Mâlikî, there is 1 form of lafaz amar, namely in the form of fi'il amar in jama', then the shafi'i Madhhab in Al-Um has 5 forms of use of lafaz amar, including fi'il amar mufrad, fi'il amar jama', fi'il mudhari' with lam amar, and lafaz amar using the lafaz عَلَى, while in the book of the hambali Madhhab in the book called Al-Mughnî there are 5 forms of use of lafaz amar in the book, including: fi'il amar mufrad, fi'il amar jama', fi'il madhi with lafaz اِفْتَرَضَ, and lafaz amar using lafaz عَلَى.